2021
DOI: 10.1155/2021/3469706
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Minor Hallucinations in Patients with Parkinson’s Disease

Abstract: Purpose. As the most frequent and earliest type of psychotic phenomenon in Parkinson’s disease (PD), minor hallucination (MH) can occur before the onset of motor symptoms. This sensation may be an early predictor of severe psychotic and cognitive states and is often overlooked in clinics. This study was aimed at providing a comprehensive and in-depth understanding of MHs. Patients and Methods. Demographic information was obtained from 262 patients with PD, and a series of clinical assessment questionnaires wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…In addition, we found that the FC strength of the SFGmed and the left middle occipital gyrus correlated with RBD assessment scores and that the FC strength of the SFGmed and the right calcarine sulcus correlated with PDSS and mood assessment scores. Previous studies have found correlations between MH and RBD, sleep quality, and mood disorder (Zhong et al, 2021); thus, reduced FC between the SFGmed and the visual cortex is important in MH and may be an imaging marker of it. Since MH and the beginning symptoms of RBD such as vivid dreams and sleep disruption were reported to be warning signs of worsen cognitive impairment during the course of PD (Lenka et al, 2016), early identification and intervention of MH are significant for these patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, we found that the FC strength of the SFGmed and the left middle occipital gyrus correlated with RBD assessment scores and that the FC strength of the SFGmed and the right calcarine sulcus correlated with PDSS and mood assessment scores. Previous studies have found correlations between MH and RBD, sleep quality, and mood disorder (Zhong et al, 2021); thus, reduced FC between the SFGmed and the visual cortex is important in MH and may be an imaging marker of it. Since MH and the beginning symptoms of RBD such as vivid dreams and sleep disruption were reported to be warning signs of worsen cognitive impairment during the course of PD (Lenka et al, 2016), early identification and intervention of MH are significant for these patients.…”
Section: Discussionmentioning
confidence: 90%
“…All subjects were scored on the MoCA, rapid eye movement sleep behavior disorder screening questionnaire (Chaudhuri et al, 2002) for all PD patients was performed to assess motor symptoms and sleep conditions. As mentioned, a questionnaire (Zhong et al, 2021) was used to record the characteristics of MH in the PD-MH group in more detail.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Moreover, LEDD doses were higher in the PIGD subgroup in our study, which may lead to an increased incidence of MHs in the PIGD subgroup. However, increasing evidence suggested that the appearance of MHs represented the more aggressive PD, regardless of levodopa doses (18,50). Therefore, LEDs should be used as potential confounders for additional analysis in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that MHs may precede the onset of motor symptoms, the result may be negative. Based on a previous study, a more detailed questionnaire was used to describe the characteristics of MHs as precisely as possible (18). The severity of motor symptoms was measured by the UPDRS III and Hoehn and Yahr (H-Y) scales, while the Non-Motor Symptom Questionnaire (NMS-Quest) was used to assess nonmotor symptoms.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Parkinson's disease (PD) is the second-largest neurodegenerative disease with clinical manifestations of motor and nonmotor symptoms. As a common nonmotor symptom, minor hallucinations (MHs) have been recognized as a premotor symptom [ 1 , 2 ] and the most frequently present hallucination in PD [ 3 ]. MHs consist of presence hallucinations, passage hallucinations, and visual illusions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%